2016
DOI: 10.1111/ijfs.13099
|View full text |Cite
|
Sign up to set email alerts
|

Optimising germinated conditions to enhance yield of resveratrol content in peanut sprout using response surface methodology

Abstract: Summary Peanut sprout has associated with enhance the content of a nonflavonoids known as resveratrol, which influences a variety of functions including against cancer, cardiovascular and delaying ageing. Peanut from Liaoning province of China was used as a material to accumulate resveratrol during germination. The individual effects of soaking temperature and time as well as germination temperature, time and humidity on resveratrol accumulation in 5 days germinated peanut were investigated. Then, based on Box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Different studies show that the peanut sprouts possess the optimum amount of nutrients and other phytochemicals on varying days starting from day 5. Miao et al [12] obtained optimum resveratrol content in the peanut sprouts on day 5. Lee et al [20] found the highest resveratrol content on day 9.…”
Section: Resveratrol Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies show that the peanut sprouts possess the optimum amount of nutrients and other phytochemicals on varying days starting from day 5. Miao et al [12] obtained optimum resveratrol content in the peanut sprouts on day 5. Lee et al [20] found the highest resveratrol content on day 9.…”
Section: Resveratrol Contentmentioning
confidence: 99%
“…One hundred grams of intact seeds, in three replications, of each cultivar and the breeding line were soaked in tap water at 30°C for 10 h. The water was drained off after 10 h and the seeds were put into 3-L plastic buckets having the perforated base for sprouts production. Peanut sprouts were grown according to the method described by Miao et al [12] with some modifications. The buckets containing seeds or sprouts were sprinkled with tap water using two hoses of 1-cm diameter for 2 min every 6 h. The sprouts were grown at room temperature (22-25°C) for 9 days.…”
Section: Sprout Growingmentioning
confidence: 99%
“…Response surface methodology (RSM) serves as an effective statistical tool to optimise and improve processes which are affected by several variables (Baş & Boyacı, ; Miao et al ., ). This approach evaluates the interaction among different independent variables as well as their effects on the responses in linear and quadratic manners (Prakash Maran et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Protease activity in the peanut sprouts was measured according to the method of Miao et al [20] . One gram of fresh peanuts/peanut sprouts was combined with 8 ml 0.05 M Tris HCL buffer (pH 7.4, containing 1% PVP, 10 mM β-mercaptoethanol, and 1 mM EDTA) and ground in an ice bath.…”
Section: Methodsmentioning
confidence: 99%